Math, asked by parteek92, 1 year ago

The value of (x - y)^3 + (x + y)^3 +3(x - y)^2(x + y) +3(x + y)²(x - y) is​

Answers

Answered by ZeroX109
11

Answer:

8x^3

Step-by-step explanation:

(x - y)^3 + (x + y)^3 +3(x - y)^2(x + y) +3(x + y)²(x - y)

let (x-y) = a

and (x+y) = b

now, replace (x-y) with a and (x+y) with b.

we have,

a^3 + b^3 + 3a^2b + 3ab^2

now apply identity (a+b)^3 = a^3 + b^3 +3a^2b + 3ab^2

= (a+b)^3

again replace a by (x-y)

and b by (x+y)

we have,

(a+b)^3 = (x-y+x+y)^3

            = (2x)^3

            =  8x^3

like it if u appreciate my effort.


parteek92: soory
parteek92: wrong
ZeroX109: then can you tell me the correct answer
ZeroX109: actually according to me its looking 100% TRUE
parteek92: soory it is write
parteek92: i have seen another que
ZeroX109: OK THANKU buddy then like krdo
parteek92: done
Similar questions